1935
DOI: 10.1098/rspa.1935.0200
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption of hydrogen on tungsten

Abstract: When a gas atom or molecule strikes a solid surface it may either rebound, the collision being accompanied by an interchange of energy, or it may be adsorbed. In order to obtain a satisfactory interpretation of either type of phenomenon it is necessary to know the nature of the atoms concerned. This is comparatively easy for the gas, but the solid requires closer attention. The essential condition is that the surface of the solid is completely freed from adsorbed films of impurity before the experiment starts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

1938
1938
1970
1970

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(33 citation statements)
references
References 0 publications
2
30
0
1
Order By: Relevance
“…The first evidence for this was obtained by Roberts (1935). He measured heats of adsorption of hydrogen on tungsten surface that was considered to be quite homogeneous.…”
Section: +mentioning
confidence: 91%
See 1 more Smart Citation
“…The first evidence for this was obtained by Roberts (1935). He measured heats of adsorption of hydrogen on tungsten surface that was considered to be quite homogeneous.…”
Section: +mentioning
confidence: 91%
“…Langmuir (1918), Paneth and Vorwerk (1922) and Roberts (1935) have shown that a definite adsorption limit occurs, beyond which further molecules cannot be adsorbed readily. When the surface area is known, the limit is found to correspond to the existence of a unimolecular layer.…”
Section: +mentioning
confidence: 99%
“…The work of Roberts (1935) and Van Cleave (1938) has shown th at both these gases form chemisorbed films on tungsten, but it seems that such films can possess little or no frictional properties on the metals. This result is in harmony with the observations of Holm and Kirschstein (1936) th a t oxygen de creased the adhesion between metals, while hydrogen and nitrogen did not.…”
Section: The Influence Of Gasesmentioning
confidence: 99%
“…However, in the case of tungsten some information is available. Langmuir and Villars (1931) have shown th a t the oxide film on this metal begins to evaporate a t 1500° K. Later, Roberts (1935) made a thorough study of the conditions under which the surface of this metal may be cleaned, and found th at a tungsten wire had to be heated in excess of 2000° K before the oxide film was completely removed. Bosworth and Rideal (1937) have observed th a t the fraction of a tungsten surface which remains covered by adsorbed oxygen a t 1600° K is only 0*3.…”
Section: R E S U L T Smentioning
confidence: 99%
See 1 more Smart Citation